ESTIMATING ENVIRONMENTAL IMPACT FROM CABLE WASTE IN DEWA - Al-Amiri, Reem (2016)
The study topic is the use of the lifecycle assessment for estimating the environmental impact from cable waste in Dubai Electricity and Water Authority (DEWA). The topic is of interest given the fact that asset management for the utility cables is a key goal in achieving performance that is highly sustainable, while the cables are being kept in service the longest possible. This is only achievable with asset management that is dedicated throughout the lifecycle of the cable, including the procurement stage, operation, installation, maintenance as well as replacement. With that view, the main objective of the analysis is assessing the environmental impact of the cable materials and identifying how the LCA can be applied to address the cable waste problem. That entails identifying the major waste contributing materials among the XLPE, copper, aluminum and PVC. Regarding the applied methodology, the Life Cycle Asset is used. The approach is defined as a means for a systematic evaluation of service or product system environmental aspect through all the stages of their life cycle. In addition, the LCA offers an adequate mechanism for the decision support on the environment. The performance of a reliable LCA is also identified as important in achieving the economy in Asset life cycle. In respect to the authority being analyzed, the DEWA case is used. DEWA is a provider of services for electric power systems. It was established in 1992. Its operations include designing and commissioning of switching as well as protection products for power generation, transmission and distribution. Finally, the method applied in the empirical analysis involves identifying the quantity of the waste that was removed from cable used in the field. Further, the analysis entails allocating an environmental impact factor for each material based on the 2008 metals impact report. Further, it entails identifying the proportion of the material use in the Authority ’s operations based on the 2008 global materials use in cables production. With that, the total impact of each material is computed in view of the impact factor and the proportion of use. In view of the analysis findings, it is indicated that the XLPE waste problem is the most prevalent compared to the other waste materials. Thus, recommendations are made for the authority to focus on using less of the material or use a lighter quality that would have reduced impact. The recommendation is in line with the extreme importance for the asset management for any organization that is asset intensive. This has a huge asset life influence and it fulfills a business objective. Finally, the key benefits that the study identified would accumulate for the business with effective asset management include cost, risk and performance balancing and corporate objective aligning with the spending decisions.